1448. Socio-demographic and clinical characteristic of Tuberculosis in Tor Vergata Hospital, Rome: a 9-years analysis. (15th December 2022) - Benedetta, Rossi
Abstract: Background: Tuberculosis (TB) represents one of the major global health problems worldwide. Italy is a low-incidence country for TB with a prevalence of 23% of extrapulmonary forms (EPTB). Migrants coming from high TB incidence country might modify local epidemiology. Methods: We conducted a retrospective, single-center observational study including data from patients with an active TB diagnosis, admitted to the Infectious Diseases Department of Tor Vergata Hospital, Rome, from 2013 to 2021 Results: The study included 210 patients with a median age of 38 years (IQR 36-46), 77% were male, 74% were not Italians (31% Africans, 26% East-Europeans, 11% Asian and 6% Latin Americans) 28% of patients were immunocompromised: 5.7% tested positive for HIV, 4.7% were on immunosuppressive treatment with anti-TNF drugs, 4.7% had onco-hematological diseases, 15.7% had severe malnutrition. PPD, performed in 90 patients, resulted positive in 77; QuantiFERON-TB Gold (QTF), performed in 187 patients, resulted positive in 149, indeterminate in 9 and negative in 29 patients. 43% of patients presented with EPTB, of whom 38 had lymph node TB, 24 bone TB, 20 pleural TB, 17 abdominal TB, 9 central nervous system TB and 23 were disseminated TB (≥3 systems involved). EPTB forms, compared to pulmonary TB (PTB), were significantly more common in males (p=0.027), of younger age (p< 0.001), from Africa and Asia (p< 0.01). Immunosuppression was not significantly associated with EPTB. Lymphocytes and monocytes absolute count were significantly lower in patients with EPTB, compared to PTB (Fig. 1). Lymphocyte subpopulations were analyzed in 89 patients, showing a significantly lower CD4 count in patients with EPTB, compared to PTB (p=0.006) (Fig. 2). QTF tube 2 titer was higher in the EPTB forms (p=0.024), no association was found with QTF tube 1 (p=0.069) and QTF mitogen (p=0.118) with TB localization. (Fig.3) QTF negativity rate was higher in patients with EPTB (p=0.063). Lymphocytes and monocytes in extrapulmonary TB (E) and pulmonary TB (P) Analysis of lymphocytes subpopulations in extrapulmonary TB (E) and pulmonary TB (P) Analysis of Quanti-FERON titer in extrapulmonary TB (E) and pulmonary TB (P) Conclusion: In our cohort, there was a high prevalence of EPTB (43%), mainly diagnosed in young, otherwise healthy men from high-endemic areas, highlighting the connection of EPTB with socio-demographic determinants. Although QFT negativity rate was higher in EPTB patients, a prudent interpretation of QFT might be needed in patients with high suspicion of EPTB. Disclosures: All Authors : No reported disclosures.